Public Service of Religious Courts in Indonesia Based on the E-Court Application - Sugeng Cahyono, Anang; Zauhar, Soesilo; Domai, Tjahjanulin; ., Siswidiyanto (KnE Social Sciences, 2023)
This study aimed to compare the religious courts’ service quality using qualitative methods with the PIECES analysis approach. They electronically facilitated proceedings through the e-filling application or online case registration, e-payment of litigation fees, e-summons, and e-litigations. The courts achieved this through Supreme Court Number 3 of 2018 concerning the Administration of Cases in Courts Electronically, complemented by the Regulation of the Supreme Court Number 1 of 2019 concerning the Administration of Cases and Trials in Courts. The results showed that all services at the Class IA Religious Court Tulungagung have used the e-Court application. However, there are various obstacles, such as user dependence on the internet network, inaccessible geographical locations, and network errors. Keywords: Public Service, e-Court Application